Case report: A rare case of isolated sigmoid Rosai-Dorfman disease on contrast-enhanced CT and 18F-FDG PET/CT - Qi, Wanling; Luo, Zhehuang; Shao, Mingyan; Chen, Min; Liao, Fengxiang; Hu, Linfeng (Frontiers in Medicine, 2024)
Rosai-Dorfman disease (RDD) is an uncommon histiocytic disorder that occurs in nodal and/or extranodal sites. Extranodal RDD exhibits a wide range of clinical and radiological presentations, frequently leading to misdiagnoses. Involvement of the gastrointestinal (GI) system is uncommon, accounting for less than 1% of the reported cases. Here we present a case of a 54-year-old male who complained of abdominal distention and was diagnosed with RDD affecting the sigmoid colon, manifesting as a sigmoid mass. The patient had a past medical history of liver transplantation due to hepatocellular carcinoma (HC). This report details the multiphase contrast-enhanced computed tomography (CT) and fluorodeoxyglucose (18F-FDG) positron emission tomography (PET-CT) imaging findings of RDD involving the sigmoid colon without lymphadenopathy, and a review of the relevant literature is provided.